'He who pays the piper calls the tune': university key performance indicators post COVID-19. (2nd November 2022) - O'Connell, Brendan T.
ABSTRACT: This paper is analytical and primarily focuses at the individual academic level. It examines the drive for academics to meet narrowly defined key performance indicators that is potentially leading to sub-optimal outcomes such as universities diverging from acting for the wider betterment of society and reduced quality of teaching and learning. This trend has been exacerbated by the COVID-19 crisis. For example, a heavy reliance on online learning has potentially reduced student engagement where these programmes have not been designed and implemented well. If academic performance is primarily judged by research outcomes, but academics face increasing expectations around developing high-level, online teaching materials, then this creates a tension for them. Turning to the ways forward, universities need to develop staff performance evaluation systems that re-orientate towards a broader set of indicators of success, and academics need more input into the performance indicators that are cascaded down to them.